Hypertension Knowledge and Willingness of Government Officials in a Southwestern Nigerian City to Self-Monitor Blood Pressure (2019)
"Self-monitoring of blood pressure (BP) is indispensable for the prevention and management of hypertension. Attitude and willingness to self-monitor BP have not been well investigated in Nigeria. This study investigated hypertension knowledge, attitude, and willingness of government officials in a southwestern Nigerian city to self-monitor BP. The study was a descriptive cross-sectional survey and 280 respondents completed a pretested, semistructured questionnaire. Data were analyzed using descriptive statistics and v2 test. Mean age was 35.7 10.6 years, 57.5% were women and 72.1% had tertiary education. Majority (65.7%) had poor knowledge about hypertension, only 1.8% recognized its symptomless nature. Majority (77.9%) had positive attitude toward being trained to self-monitor BP, while 82.1% were willing to buy self-monitoring devices. Hypertension knowledge was associated with age and marital status (p <.05), while attitude was associated with willingness to self-monitor BP (p <.05). Population-wide, educational interventionsshould be intensified to improve hypertension knowledge and enhance skills to self-monitor BP."